If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + 8(x + 2) = 6(1 + x) + -1 Reorder the terms: 5 + 8(2 + x) = 6(1 + x) + -1 5 + (2 * 8 + x * 8) = 6(1 + x) + -1 5 + (16 + 8x) = 6(1 + x) + -1 Combine like terms: 5 + 16 = 21 21 + 8x = 6(1 + x) + -1 21 + 8x = (1 * 6 + x * 6) + -1 21 + 8x = (6 + 6x) + -1 Reorder the terms: 21 + 8x = 6 + -1 + 6x Combine like terms: 6 + -1 = 5 21 + 8x = 5 + 6x Solving 21 + 8x = 5 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 21 + 8x + -6x = 5 + 6x + -6x Combine like terms: 8x + -6x = 2x 21 + 2x = 5 + 6x + -6x Combine like terms: 6x + -6x = 0 21 + 2x = 5 + 0 21 + 2x = 5 Add '-21' to each side of the equation. 21 + -21 + 2x = 5 + -21 Combine like terms: 21 + -21 = 0 0 + 2x = 5 + -21 2x = 5 + -21 Combine like terms: 5 + -21 = -16 2x = -16 Divide each side by '2'. x = -8 Simplifying x = -8
| y*2=116-40 | | 2(5-8)+9= | | 11=-n/7 | | 7/x=17/9 | | y*2=116-28 | | y*2=116-30 | | 10a+5(a-3)=-15 | | y*2=116-24 | | y*2=116-25 | | 64x^3-100x=0 | | 56x^3+64y^3=0 | | -6/(-2)(4) | | 7x-9=8x+7 | | x/10-25=5 | | 3(-4)(-4)(0)(-3) | | 3(-4)(-4)(0)(-3)= | | 5(x+1)=-10(2x-4+5x-6) | | X/44=-47+21 | | X+x+20 | | 1/5(10x-2)=3 | | 2+3(3x-4) | | 8k-2=4; | | 3x+15=-50 | | 8(y-2)=6y-24 | | -20*-7= | | 2(r+6)= | | (3a+2)(2a-7) | | 10-5x=10x+5(x-6) | | 4y=3(y+4) | | 7x^2-24x+24=0 | | 7x^2-24x+24 | | f(t)=0.51t^2-10.2t+68.2 |